In vitro and Molecular Study of Synergistic Impact of Eugenol and Fosfomycin against Clinically-isolated, Fosfomycin-Resistant Escherichia coli - Ibrahim, Ali Attaallah; Mohammed, Rana Kadhim (Iraqi Journal of Science, 2025)
Antibiotic resistance is a significant problem for which new treatments are required. There is growing concern about Fosfomycin resistance in Escherichia coli; understanding this resistance will help develop effective treatment strategies and preserve the efficacy of antibiotics. This study aimed to investigate the synergistic effects of Eugenol and Fosfomycin against Uropathogenic Escherichia coli (UPEC) and their possible potential as co-treatment. This study identified and isolated UPEC isolates from urine samples, with 63.6% being identified as UPEC. Antibiotic susceptibility tests showed that 99.3% of the UPEC isolates were resistant to multiple types of antibiotics [multidrug-resistant (MDR)]. The study examined the antibacterial properties of Fosfomycin and Eugenol using the parameters of agar well diffusion, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), fractional inhibitory concentration index (FICI), and time-kill curves. The MIC for Fosfomycin was 512-1024 µg/mL and for Eugenol was 1.25-5 µg/mL, while the MBC for Eugenol was 5-10 µg/mL and for Fosfomycin was 2048 µg/mL. Synergistic effects were considerable, where the addition of Eugenol at 1/4 MIC concentration resulted in 1/8 MIC of Fosfomycin. . The highest bactericidal activity for most UPEC isolates was recorded at 4-8 hours using Eugenol, 8-12 hours using Fosfomycin, and 4-8 hours using co-treatment. The study also used molecular assays to identify the expression levels of Fosfomycin resistance genes (murA, glpT, and cyaA) under different treatments, which revealed positive espression in all the isolates. The results showed variable gene expression changes in response to the different treatments. In conclusion, this study shows that Eugenol and Fosfomycin co-treatment is effective against UPEC.